Forecasting-Based Policy Recommendations to Anticipate the Threats of Ministry of Marine Affairs and Fisheries Regulation No. 7 of 2024 on the Rising Smuggling of Lobster Seedlings - Ramadhani, Rizqi; Wulansari, Dewi; Legowo, Krisno (CV RIFAINSTITUT, 2025)
Ministerial Regulation of Marine Affairs and Fisheries No. 7 of 2024 legalizes the export of lobster seeds (benur) under joint ventures, but its implementation has triggered unintended consequences, notably the escalation of smuggling practices. This situation highlights a gap between policy objectives (das sollen) and actual outcomes (das sein). Objective: This research aims to analyze potential threats of lobster seed smuggling using a forecasting approach and to provide long-term policy recommendations. Method: A mixed-method forecasting design was applied by combining historical trend analysis, the Delphi method, and scenario building. Data were collected from government reports, academic literature, and expert interviews. Validity was ensured through triangulation, while reliability was strengthened using expert consensus measured by Kendall’s W coefficient. Results: The findings show a doubling of smuggling activities between 2020 and 2024. Projections indicate that under the baseline scenario, smuggling will continue to rise steadily; under the tight enforcement scenario, growth slows significantly due to regulatory and enforcement improvements; while under the loose enforcement scenario, smuggling escalates sharply as a result of weak oversight and high global demand. Conclusion: Regulation No. 7/2024 may worsen smuggling if not supported by consistent law enforcement, interagency coordination, and demand management strategies. Recommendation: The government should integrate forecasting into policymaking, strengthen maritime surveillance, provide alternative livelihoods for coastal communities, and enhance regional cooperation to reduce global market pressures.